Why don't the poor save more? evidece from health savings experiments - Dupas, Pascaline (2013)
Presents data from a field experiment in Kenya, that documents that providing individuals with simple informal savings technologies can substantially increase investment in preventive health and reduce vulnerability to healt shocks.